2022
DOI: 10.1155/2022/6450527
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell-Derived Neuron-Like Cell Transplantation Combined with Electroacupuncture Improves Synaptic Plasticity in Rats with Intracerebral Hemorrhage via mTOR/p70S6K Signaling

Abstract: Previous studies have shown that the combination of mesenchymal stem cell (MSC) transplantation and electroacupuncture (EA) stimulation is a neuroprotective strategy for treating intracerebral hemorrhage (ICH). However, the underlying mechanisms by which the combined treatment promotes neuroprotection remain unclear. This study was designed to investigate the effects of the combined treatment on synaptic plasticity and elucidate their underlying mechanisms. Therefore, rat ICH models were established by injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 81 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…By using 18 F-FDG micro-PET scanning to detect the bleeding area [9][10][11], the results showed that Ea treatment reduced the hemorrhagic focal area. This is significant as the extent of a brain injury is closely associated with brain edema and the duration of edema [12,13]. Our results showed that the brain water content increased in rats by Day 7 after ICH and that Ea therapy was associated with brain edema alleviation.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…By using 18 F-FDG micro-PET scanning to detect the bleeding area [9][10][11], the results showed that Ea treatment reduced the hemorrhagic focal area. This is significant as the extent of a brain injury is closely associated with brain edema and the duration of edema [12,13]. Our results showed that the brain water content increased in rats by Day 7 after ICH and that Ea therapy was associated with brain edema alleviation.…”
Section: Discussionmentioning
confidence: 56%
“…The mNSS test was used to assess neurobehavioral deficits through a series of motor, sensory, balance, and reflex measurements [10]. The score of 0-18 indicated the degree of injury (normal score, 0; slight injury, 1-6; moderate injury, 7-12; serious injury, [13][14][15][16][17][18]. ICH rats with final scores of higher than 8 were included in subsequent experiments.…”
Section: Ea Treatmentmentioning
confidence: 99%
“…The combined intervention of mesenchymal stem cell (MSC) transplantation and EA is a neuroprotection strategy for intracerebral hemorrhage (ICH) [ 49 ]. The combination of two methods, by relieving cerebral edema and glial scar, promotes neuronal and oligodendrocyte survival, activates mammalian target of rapamycin (mTOR) / 70 kDa ribosomal protein S6 kinase (p70S6K) proteins signaling, and enhances synaptic plasticity [ 50 ]. Relevant evidence suggests that the effect of acupuncture in ICH may be related to the modification of microglia polarization via the miR-34a-5p/Krüppel-like factor 4 (Klf4) signaling pathway [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ICH animal model was established following the methodology outlined in our previous study. 28 , 36 Shortly, anesthetized mice were secured by immobilizing the bilateral external ear hilum and incisor to a stereotaxic apparatus. The anterior and posterior fontanels were positioned at the horizontal plane to ensure stability.…”
Section: Methodsmentioning
confidence: 99%